Hubungan Kepemimpinan Visioner terhadap Mutu Layanan Sekolah di SMPN Satu Atap 01 Nanggung Bogor - Siti Halimah; Ima Rahmawati; Hana Lestari (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
The purpose of this study was to determine the relationship of visionary leadership to the quality of school services at SMPN 01 Nanggung. This study used a quantitative approach with a sample of 20 respondents. Retrieval of data using an questionnaire with a likert scale as a measure. And data analysis techniques using the SPSS 21 application. Based on the results of the simple linear regression test, it was obtained a significant value of 0.000 <0.05, it can be concluded that there is a positive and significant connection between visionary leadership to the quality of school services . It is demonstrated that the increasingly strong connection of visionary leadership, then of the quality of school services further increase. Keywords: visionary leadership,school service quality